Network Governance: Participatory Approach to Contribute at Singkawang Tourism Policy (Case on Cap Go Meh Event) - Patriani, Ira; Burhan, Rasidi; Haryaningsih, Sri; M.Wuysang, Julia; Rahmawati, Rahmawati (Indonesian Association for Public Administration (IAPA), 2023)
This paper tells about Singkawang city which embraces a harmonious multicultural society with three major ethnicities, namely TIDAYU (Chinese, Dayak and Malay) and other entities existing besides government. This area has rich cultural diversities give positive advantages for tourism development and bode well for significant local economic growth. Among others, the Cap Go Meh (Chinese religious tradition) is considered to the biggest and international scale event that involves the all of ethnics participatori through networking resources. This event has unique features that attract Chinese diasporas from other regions in Indonesia and neighboring countries. For that reason, the actors involved in this event constitute various social, economic, and political backgrounds. This paper focused on how Singkawang local government can develop a distinctive tourism policy to address the specific multi stakeholder interactions using a qualitative approach. It found that in the context of Singkawang tourism policy, the interaction and dynamic patterns among policy actors are developed through linear individual cooperation. Within this pattern, the interaction amongst policy actors tend to involve certain individuals who have authority in controlling resources regardless of their origin or organizations. In fact, this pattern is very strongly based on family relationships or friendships found in both public and private domains. It has shown that developing Singkawang tourism policy should be developed based on network governance (participatory from resources) and good stakeholder engagement.